Asal-Usul Bangsa Arab: Studi Kritis atas Pemikiran Louis Awad - Musda Asmara (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This purpose of this article is to describe the Arabian History, the origin and critics on the deviation to the history done by Louis Awad to the Arab society. In the history, the arabian was related to the Semitic sociaty who descent from Sam bin Nuh. The data of this tudy is based on a library research with Muqoddimah Fi Fiqh al-Lughoh al-Arobiyah by Dr. Louis Awad as the main source. In his book, Dr. Louis Awad explains a contradictive explaination from the historical facts, he even avoid the facts. He assumes that Arabian is not related to the Semitic nation, but come from the Indo- Europian race. Further he said the origin of Semiyah is the Indo-Europian race. It is certainly a form of fraud, which aims to obscure the history, to demean the position of the Arabian, which is the ultimate objective, is to put the Arabic, the Qur'an in a low position.